(untitled) (Architecture Image Studies, 2025)
The sustainability of blended learning in private universities has become a critical concern following the Covid-19 pandemic, as this learning model combines face-to-face and online methods, offering flexibility and adaptability to technological developments. Case studies at Esa Unggul University (UEU), Mercu Buana University (UMB), and Tarumanagara University (UNTAR) provide a concrete overview of the scope of blended learning implementation and the challenges faced in maintaining its sustainability in private universities. This research aims to examine how the implementation of blended learning in private universities, especially at Esa Unggul University (UEU), Mercu Buana University (UMB), and Tarumanagara University (UNTAR). This research uses a case study approach with mixed methods to examine sustainability. Blended learning at three private universities in Jakarta: Esa Unggul University, Mercu Buana University, and Tarumanagara University. Data were collected through interviews with academic and administrative stakeholders and questionnaires with students in employee classes, supported by secondary data such as online learning documentation. Analysis was conducted thematically and quantitatively using SPSS, resulting in a comprehensive overview of the supporting factors and challenges in the implementation blended learning at the three universities. The research results show that implementing blended learning post-pandemic requires system support, digital skills, and institutional commitment to address challenges and maintain sustainability. Adaptation is carried out through development strategies, strengthening human resources, and optimizing learning methods. Sustainability prospects depend on technological readiness, teaching quality, and student engagement, although several aspects such as technical skills and feedback, need improvement.